Enantioselective synthesis of (+)-(S,S)-reboxetine - Siddiqui, Shafi A.; Narkhede, Umesh C.; Lahoti, Rajgopal J.; Srinivasan, Kumar V. (Synlett, 2006)
An efficient enantioselective synthesis leading directly to (+)-(S,S)-reboxetine has been described from commercially available trans-cinnammyl bromide using Sharpless asymmetric dihydroxylation as the key step.
Keywords: coupling; Dihydroxylation; Hydrogenation; reboxetine; trans-cinnamyl bromide

Enantioselective synthesis of (S)-dapoxetine - Siddiqui, Shafi A.; Srinivasan, Kumar V. (Tetrahedron-Asymmetry, 2007)
An efficient enantioselective synthesis leading directly to (+)-(S)-dapoxetine has been described for the first time using Sharpless asymmetric dihydroxylation, Barton-McCombie deoxygention, and Mitsunobu reaction as the key steps. (C) 2007 Published by Elsevier Ltd.